The impact of the technological surveillance in the projection of the investigations of ethanol production from sugarcane bagasse. Part I - Claro, Mirelis; Mesa Garriga, Leyanis; González Suárez, Erenio; Galian, C (Centro Azúcar Journal, 2010)
The work has as main objective to evaluate the impact of the technological surveillance of the ethanol production from sugarcane bagasse like lignocellulosic residual in the formulation and search of new projects and strategic alliances with the productive sectors. Also, it offers a theoretical analysis on the current scenario in the thematic one, the paper of the call society of the information and the administration of the external information in the management of the knowledge and projects linked to the thematic one. The analysis of the technological surveillance of the process gives the possibility to identify the investigation necessities to short, medium and long term and this way to trace investigative strategies to give execution to the objectives layouts.